Building Strong Communities against land and water grabbing - Katosi, Women Development Trust (KWDT) (Financial support from the International Development Research Centre (IDRC)-Canada, 2017)
Small scale fishers in Uganda continue to struggle for access to the land and water resources on which they depend for their livelihoods, and are increasingly at risk of losing access to these resources entirely. Competing visions of development and the interests of wealthy investors have led to numerous cases of land grabbing in the country, where smallholders are legally or illegally displaced from land to which they have a legitimate claim. A number of features of the policy and legal framework in Uganda allow this practice to continue, endangering the livelihoods of small fishers and other rural residents. Katosi Women Development Trust has conducted action research into the access to land and other resources in selected fishing communities in Uganda, investigating the drivers of land and water grabbing. This investigation has revealed a number of policy recommendations which could strengthen the rights of small-scale fishers and help to combat displacement and dispossession.
Keywords: Communities; Land; Water